1998
DOI: 10.1902/annals.1998.3.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth: Associations With Genital and Possibly Oral Microflora

Abstract: Opportunistic pathogenic microbes are indigenous to the female lower genital tract and etiologic in many types of pelvic infections and, apparently, a portion of preterm birth (PTB) cases. Bacterial vaginosis (BV) is a clinical syndrome based on an altered genital microflora in which Gardnerella vaginalis; anaerobic species primarily among Prevotella, Porphyromonas, Bacteroides, Peptostreptococcus, and Mobiluncus; Mycoplasma hominis; and Ureaplasma urealyticum become predominant in vaginal secretions. This BV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
1
21

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(176 citation statements)
references
References 68 publications
(13 reference statements)
3
148
1
21
Order By: Relevance
“…However, this study failed to find such an association between pregnancy outcome and reported urinary tract infection, perhaps due to problems in diagnosing maternal genito-urinary tract infection, which can often be subclinical. 21 Other medication taken in early pregnancy was also associated with poor outcome: it may be regarded as a surrogate marker for medical problems which may themselves affect pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study failed to find such an association between pregnancy outcome and reported urinary tract infection, perhaps due to problems in diagnosing maternal genito-urinary tract infection, which can often be subclinical. 21 Other medication taken in early pregnancy was also associated with poor outcome: it may be regarded as a surrogate marker for medical problems which may themselves affect pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…During periodontal infection, its cell mass increases as much as 10,000-fold, making it one of the most abundant anaerobic species in the diseased sites (48). F. nucleatum is also one of the predominant anaerobes associated with preterm birth, having been frequently isolated from amniotic fluids and placentas of women delivering prematurely (27). F. nucleatum may originate in the oral cavity and be transmitted to the uterus via a hemotogenous route.…”
mentioning
confidence: 99%
“…This is undoubtedly due to the presence of highly effective fetal defense mechanisms that serve to limit the bacterial infection of placental tissues. The placenta is a highly selective mechanical and immunological barrier against the dissemination of infectious agents by hematogenous routes or by the ascending route from the vagina (18). These defenses serve to limit both the degree and frequency of bacterial colonization within the placenta.…”
mentioning
confidence: 99%